Ittefaq [videorecording (DVD)] - Chopra, Abhay; Malhotra, Sidharth, 1985-; Khanna, Akshaye; Sinha, Sonakshi, 1987- (Reliance Big Entertainment, 2017)
An acclaimed writer and a young homemaker become the prime suspects in a double murder. Police officer Dev must figure out who's telling the truth when both offer conflicting stories about the events of that fateful night.